Subgenual cingulate cortex activity in predicting risk factor and treatment response in depression - Alva S. A. Supit; Ireine Roosdy (WMJ (Warmadewa Medical Journal), 2018)
Major depressive disorder (MDD) contributes significantly to morbidity, disability, and decreased quality of life, despite the expansion of treatment options. This, in part, is caused by a lack of valid, applicable, and reliable biomarkers to predict the risk, treatment response, and prognosis of depression. In recent years, the anterior cingulate cortex, in particular pars subgenual (sgACC), has received much attention due to its potential utilization as a neural endophenotype for depression. This essay will discuss the functional activity of sgACC, mostly by functional magnetic resonance imaging, in relation to predicting risk for developing depression, predicting patient response-to-treatment, and eventually, to create a platform for personalized psychiatric approach to each patient. The caveats and conditions need to be met will also be discussed, in order to firmly establish sgACC activity as a valid biomarker for depression.